2022
DOI: 10.2147/idr.s358116
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of High Prevalence of Extended-Spectrum Beta-Lactamase and Carbapenemase Producing Acinetobacter Species and Pseudomonas aeruginosa Among Hospitalized Patients at Dessie Comprehensive Specialized Hospital, North-East Ethiopia

Abstract: Background The emergence of extended spectrum beta lactamase and carbapenemase production of Acinetobacter and Pseudomonas aeruginosa is a great concern and major cause of nosocomial infections due to its ability to production of extended spectrum beta lactamase and carbapenemase enzymes. Objective To assess Emergence of high prevalence of extended-spectrum beta-lactamase and Carbapenemase producing Aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 52 publications
3
8
1
2
Order By: Relevance
“…In this retrospective study, we analyzed the five-year antimicrobial resistance profiles of P. aeruginosa and Acinetobacter species with an emphasis on the prevalence and trends of carbapenem resistance at the Ethiopian Public Health Institute, Addis Ababa, Ethiopia. The prevalence of carbapenem-resistant Acinetobacter species in the current study was 61%, which is consistent with the findings of the study from Pretoria, South Africa (63%), 27 and Jimma, Ethiopia (56.4%), 25 however, it is higher than the findings of studies from Lusaka, Zambia (18.2%), 28 Switzerland (9.2%), 29 North-East, Ethiopia (34.5%), 18 Sidama, Ethiopia (9.9%), 22 North Gondar, Ethiopia (20.77%), 24 Northwest Ethiopia (33.3%), 17 and Dessie, Ethiopia (43.8). 16 The variation could be attributed to differences in study design, the number of isolates analyzed, the types of specimens considered, and the amount of data analyzed, as some studies only analyzed fewer data, while others analyzed a large amount of national antimicrobial resistance data, geographical differences, and antibiotic prescription policy differences.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this retrospective study, we analyzed the five-year antimicrobial resistance profiles of P. aeruginosa and Acinetobacter species with an emphasis on the prevalence and trends of carbapenem resistance at the Ethiopian Public Health Institute, Addis Ababa, Ethiopia. The prevalence of carbapenem-resistant Acinetobacter species in the current study was 61%, which is consistent with the findings of the study from Pretoria, South Africa (63%), 27 and Jimma, Ethiopia (56.4%), 25 however, it is higher than the findings of studies from Lusaka, Zambia (18.2%), 28 Switzerland (9.2%), 29 North-East, Ethiopia (34.5%), 18 Sidama, Ethiopia (9.9%), 22 North Gondar, Ethiopia (20.77%), 24 Northwest Ethiopia (33.3%), 17 and Dessie, Ethiopia (43.8). 16 The variation could be attributed to differences in study design, the number of isolates analyzed, the types of specimens considered, and the amount of data analyzed, as some studies only analyzed fewer data, while others analyzed a large amount of national antimicrobial resistance data, geographical differences, and antibiotic prescription policy differences.…”
Section: Discussionsupporting
confidence: 91%
“…Infection and Drug Resistance 2023:16 1388 (12.9%) Table 3. Our findings are in line with the findings of studies from Ethiopia; Sidama, Ethiopia, 22 and Northeast Ethiopia 16,18 which reported higher resistance to cephalosporins (ceftazidime and cefepime) and lower resistance to aminoglycosides (amikacin, gentamicin, and tobramycin). The high prevalence of extended-spectrum cephalosporin resistance observed against these organisms could be attributed to the overprescription of these antibiotics in Ethiopia, even for minor infections.…”
Section: Dovepresssupporting
confidence: 92%
See 2 more Smart Citations
“…Seas et al(22) confirma que la cepa Staphylococcus aureus se encuentra distribuida en gran parte de América Latina. Así como el género Staphylococcus es de gran inquietud, el género Acinetobacter también; es el principal causante de infecciones nosocomiales, se asocia con varias epidemias y altas tasas de mortalidad y específicamente, Acinetobacter baumanii es resistente a múltiples antibióticos(23).…”
unclassified